Moral Value in Charlotte Bronte’s Novel Jane Eyre - Susana, E (KnE Social Sciences, 2018)
This research is intended to describe the moral values based on the protagonist of the novel Jane Eyre written by Charlotte Bronte. The objectives of this research are to describe the moral values, referring to a person who is determined to follow a meaningful life patiently following moral values in his life without the fear of getting judged and hence standing out in the crowd. The researcher uses a descriptive qualitative method in this research applying content analysis proposed by Sugiyono (2017). The theory applied in this research is adopted from Hurlock (1997). The primary data were derived from a document or record containing first hand information or original data on the topic. The data were collected from libraries and therefore this research also applied library research. The findings indicate that the protagonist could practice the three kinds of moral values; namely patience, sincerity and responsibility, which may also be followed by anyone. Keywords: moral value, patience, sincerity and responsibility.